Multi-wavelength holographic profilometry - art. no. 60272L - Barbosa, E. A.; Gesualdi, M. R.; Muramatsu, A. (Spie - Int Soc Optical Engineering, 2006)
A novel method for surface profilometry by holography is presented. We used a diode laser emitting at many wavelengths simultaneously as the light source and a Bi12TiO20 (BTO) crystal as the holographic medium in single exposure processes. The employ of multi-wavelength, large free spectral range (FSR) lasers leads to holographic images covered of interference fringes corresponding to the contour lines of the studied surface. In order to obtain the relief of the studied surface, the fringe analysis was performed by the phase stepping technique (PST) and the phase unwrapping was carried out by the Cellular-automata method. We analysed the relief of a tilted flat metallic bar and a tooth prosthesis.